Дослідження забезпечення підвищення ефективності бізнес-процесів Call Center - Лук’янов, О. І.; Сабурова, С. О. (ХНУРЕ, 2025)
Research of the next-generation cloud Call Center technology has been conducted. A cloud Call Center provides improved performance parameters through flexibility, additional capabilities, and lower ongoing costs. To maximize the benefits for companies’ business operations, there is a software solution that is reliable and secure to implement with a full set of integrated features: a user-friendly web interface to increase agent productivity with high-quality customer service, rather than being bogged down in usability issues and complex training.
Keywords: бізнес-процес; Call Center